2008
DOI: 10.1002/cd.210
|View full text |Cite
|
Sign up to set email alerts
|

Social class and the experience of work-family conflict during the transition to adulthood

Abstract: The challenges of juggling work and family responsibilities are well known, but there has been little attention to the distinctive work and family experiences of young adults. This chapter explores how class affects young adults' exposure to work-family conflicts and the strategies they use to manage their work and family responsibilities. Using data from a recent cohort of young adults, we find class and gender variations in work and family roles and work-family conflict. Early family formation, coupled with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 39 publications
2
14
0
Order By: Relevance
“…In accordance with Ammons and Kelly (2008), we expected that emerging adults following a trajectory of showing low efficacy in dealing with work-partnership conflicts with limited growth over time would exhibit higher and increasing stress levels in the work domain and also greater and more frequent work-to-partnership and partnership-to-work conflicts, mainly due to their lack of progress in competence. Gianakos (1999) found that individuals with higher occupational self-efficacy showed stable and committed patterns in their career histories.…”
Section: Research Questionsmentioning
confidence: 79%
“…In accordance with Ammons and Kelly (2008), we expected that emerging adults following a trajectory of showing low efficacy in dealing with work-partnership conflicts with limited growth over time would exhibit higher and increasing stress levels in the work domain and also greater and more frequent work-to-partnership and partnership-to-work conflicts, mainly due to their lack of progress in competence. Gianakos (1999) found that individuals with higher occupational self-efficacy showed stable and committed patterns in their career histories.…”
Section: Research Questionsmentioning
confidence: 79%
“…Kelly and Ammons (2008) find that young people with lower educational attainments experience more family-to-work interference, given their early family formation and poor working conditions (e.g., limited control over work hours). Somewhat ironically, “family friendly” work policies and benefits are more available to higher income young workers who need them less.…”
Section: Extension Of the Yds To Multiple Facets Of Transition To Adumentioning
confidence: 90%
“…There is limited evidence from representative studies of North America, especially in the Canadian population. Ours is among the first that we know of to explore these associations with representative Canadian survey data (for some American exceptions, see Carr, 2002;Maume, 2006;Mennino & Brayfield, 2002;Sayer, 2005). Work-family conflict is considered bidirectional, where work intrudes on family time and expectations (work-to-family conflict) versus the opposite (family-to-work conflict).…”
mentioning
confidence: 99%